Expression of BVDV E2 protein in CHO-S cells and development of an indirect ELISA for serological detection - Wang, Jiahui; Zhang, Ao; Hou, Zhiwei; Tan, Bin; Zhang, Shuqin (Frontiers in Cellular and Infection Microbiology, 2025)
Bovine viral diarrhea virus (BVDV) causes ongoing economic losses to the livestock industry. Monitoring antibodies via enzyme-linked immunosorbent assay (ELISA) is a key tool for ensuring the eradication of BVDV from cattle herds. We developed an indirect ELISA (rE2-iELISA) using CHO-S-expressed recombinant E2 protein, the major immunogenic glycoprotein mediating viral attachment and immune evasion. Optimized assay conditions included: 0.4 μg/well antigen coating, 5% BSA blocking, 1:100 serum dilution, and 1:5000 secondary antibody dilution. The assay demonstrated exclusive specificity for BVDV-1 and BVDV-2 with detection sensitivity to 1:1,500 serum dilution. Validation revealed exceptional diagnostic performance: ROC analysis showed 0.998 AUC (cutoff=0.125), 94.8% concordance with IDEXX ELISA, and the intra- and inter-batch coefficient of variation are both less than 5%. The experimental results indicate that the indirect ELISA detection method based on BVDV rE2 exhibits good sensitivity, specificity, and stability. And a stable serological tool for BVDV surveillance and vaccine efficacy evaluation in cattle populations.